PENGEMBANGAN MODEL PEMBELAJARAN BOLA VOLI MELALUI PERMAINAN TWONET BAGI SISWA KELAS VI SEKOLAH DASAR NEGERI 1 KEDUNGCINO KABUPATEN JEPARA (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this research is to produce a product development model of learning through play volleyball twonet for students of classes VI Elementary School 1 Kedungcino Jepara district. Research Development refers to the development model of the Borg & Gall. The results of the study and discussion of expert evaluation data obtained an average of 70% (pretty good), with expert rician penjas 56% (pretty good), I 74% learning experts (good), and expert learning II 80% (good). While the results of a small pilot group obtained 84,33% (excellent) and field-testing 88,96% (excellent). It can be concluded that the development model of learning through play volleyball twonet have met the learning needs so that it can be used for students of Grade VI Elementary School 1 Kedungcino Jepara district in 2012.